Outcomes of Constrained Prostheses in Primary and Revision TKR. Issue 5 (31st May 2017) - Parkinson, Ben; Lorimer, Michelle; Lewis, Peter
Introduction: The decision to use varus/valgus constrained or hinge knee prostheses in complex Total Knee Replacement (TKR) cases is difficult. There are few publications that compare survival rates, to aid this decision-making. This study compares the survival rates of unlinked fully constrained and hinge constrained prostheses in the primary and revision settings. Methods: Data from the AOANJRR to 31 st of December 2013 was analysed to determine the survival rate of unlinked and hinge constrained TKR in the primary and revision settings (excluding the diagnosis of tumour and infection). Only first-time revisions of a known primary TKR were included in the revision analysis. Kaplan-Meier estimates of survivorship were calculated for the two categories of constraint and were matched for age and diagnosis in both primary and revision TKR situations. Hazard ratios using the Cox proportional-hazards model were used. The survivorship of individual prosthesis models was determined. Results: There were 3237 prostheses implanted during the study period that met the inclusion criteria. Of these, 1896 were for primary TKR and 1341 for revision TKR. There were 1349 unlinked fully constrained and 547 hinge prostheses for primary TKR and 991 unlinked fully constrained and 350 hinge prostheses for revision TKR. In both the primary and revision settings when matched by age, there was no difference in rates of revision for either level of constraint. When matched by indication in the primary setting, there was no difference in the rates of revision for either level of constraint. The rate of revision for both categories of constrained prosthesis was significantly higher in younger patients <55 years of age (p < 0.05). There were no differences in survival rates of individual models of constrained TKR. Conclusions: The survival rates of unlinked constrained and hinge knee prostheses are similar when matched by age or diagnosis. In complex TKR instability cases, surgeons should feel confident in choosing the appropriate prosthesis to gain a stable knee and need not be concerned that a hinge prosthesis may carry a higher revision rate.